Structural adjustment : cure or curse? Implications for Caribbean development. - Antrobus, Peggy (1990)
Analyses the impact of structural adjustment policies on women, where such policies are grounded in a gender ideology that is deeply exploitative of women's time and labour. Stresses the importance of gender as a variable in development policy making and planning.